The Association of Arterial Stiffness With Significant Carotid Atherosclerosis and Carotid Plaque Vulnerability. (August 2022) - Kadoglou, Nikolaos P.E.; Moulakakis, Konstantinos G.; Mantas, George; Kakisis, John D.; Mylonas, Spyridon N; Valsami, Georgia; Liapis, Christos D
Arterial stiffness and its valid index, the cardio-ankle vascular index (CAVI), have emerged as predictors of adverse cardiovascular outcomes. We investigated the relationship of the CAVI with significant carotid stenosis (> 50%) and the related cerebrovascular symptoms or carotid plaque echogenicity, assessed by ultrasound gray-scale median (GSM) score, at baseline and after carotid artery stenting (CAS). We prospectively enrolled 113 patients with carotid stenosis (70-99% for asymptomatic and > 50% for symptomatic participants) eligible for CAS. Age- and sex-matched individuals (n = 38) served as controls (CON). Clinical data, CAVI, and biochemical profile were obtained at baseline. Clinical assessment and CAVI measurement were performed 6 months after CAS. Compared with the CON group, the CAS group had a higher incidence of co-morbidities (diabetes, hypertension, and hyperlipidemia), higher CAVI values (9.94 ± 2.14 vs 7.85 ± .97 m/sec, P < .001), but a better lipid profile due to increased prescription of statins. The symptomatic CAS subgroup showed higher CAVI ( P < .001), high-sensitivity C-reactive protein ( P = .048), and osteoprotegerin ( P = .002) levels than the asymptomatic one. In multivariate analysis, CAVI at baseline was independently associated with the presence of significant carotid atherosclerosis (β = .695, P < .001), cerebrovascular events (β = .474, P < .001), and GSM score (β = −.275, P = .042). Raised CAVI values were independently associated with significant carotid stenosis and plaque vulnerability.